Pengaruh Kebijakan Dividen Struktur Kepemilikan dan Kinerja Keuangan Terhadap Nilai Perusahaan - Maulana, Yasir; Kartikasari, Dea; Gunawan, Wely Hadi; Komarudin, Munir Nur (www.bsi.ac.id, 2025)
During the period 2018-2022, the average PBV of automotive and component sub-sector manufacturing companies listed on the IDX was 0.31, this shows that the value of the company still needs to be increased to attract investors because ideally, good stocks for investment have a PBV value> 1. This study aims to determine the impact of dividend policy, ownership structure and financial performance on company value. The research method used in this study is the verification and descriptive method. The population in this study was 13 companies, the sample in this study used a purposive sampling technique and produced 11 samples with 55 observation data. The data collection technique used in this study used non-participant observation, this technique is used to obtain data, namely financial reports from Automotive and Component Sub-Sector Manufacturing Companies in 2018-2022. Data analysis includes descriptive analysis, classical assumption tests, panel data analysis, and hypothesis testing using the F test and t test. The research findings show that dividend policy, ownership structure and financial performance have a simultaneous impact on company value. Dividend policy has a positive impact on firm value. Ownership structure has a positive effect on firm value. Financial performance has a positive impact on firm value.